2018
DOI: 10.1017/s0950268817003090
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of non-tuberculous mycobacterial pulmonary infections in Bamako, Mali

Abstract: SUMMARY The global spread of Nontuberculous Mycobacteria (NTM) may be due to HIV/AIDS and other environmental factors. The symptoms of NTM and tuberculosis (TB) disease are indistinguishable, but their treatments are different. Lack of research on the epidemiology of NTM infections has led to underestimation of its prevalence within TB endemic countries. This study was design to determine the prevalence and clinical characteristics of pulmonary NTM in Bamako. A cross-sectional study which include 439 suspected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
2
5
0
Order By: Relevance
“… [9] Our most recent data from Mali also confirmed a 12% prevalence of NTM in all TB suspects (new and previously treated) seen at the major TB Referral Center at the Point-G Hospital of Bamako. [12] Similar data have been reported from Kenya, Burkina Faso and Nigeria. [39] , [40] , [41] Although it is not understood why MAC and other NTM diseases have been increasing worldwide including traditionally TB endemic setting, [7] environmental changes, aging, HIV/AIDS and use of immunosuppressors are known to be associated factors.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“… [9] Our most recent data from Mali also confirmed a 12% prevalence of NTM in all TB suspects (new and previously treated) seen at the major TB Referral Center at the Point-G Hospital of Bamako. [12] Similar data have been reported from Kenya, Burkina Faso and Nigeria. [39] , [40] , [41] Although it is not understood why MAC and other NTM diseases have been increasing worldwide including traditionally TB endemic setting, [7] environmental changes, aging, HIV/AIDS and use of immunosuppressors are known to be associated factors.…”
Section: Discussionsupporting
confidence: 78%
“…[9,11] In Mali, we recently reported that NTM infections was identified in 18% of clinically classified chronic TB cases. [9,12] We also reported that 12% of all patients in Mali with presumptive TB are in fact infected with NTM. [9] Nearly 73% of the NTM cases, are caused by Mycobacterium avium complex (MAC).…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…The sensitivity of the chest X-ray was 31.6% (25/79), having made it possible to find mainly cavitary images and miliaries. In the literature, approximately 36.7% of radiographic images in immunocompetent subjects are generally atypical [12]. This constitutes a limit in the diagnosis of pulmonary forms.…”
Section: Discussionmentioning
confidence: 99%